Digital Transformation in Education: The Role of Information Management in Enhancing Data-Driven Learning Quality - Dedy Sofian MZ; Sunardi Sunardi; Ahmad Fauzan (CV. Global Cendekia Inti, 2026)
Digital transformation in education has accelerated a paradigm shift from conventional instructional practices toward data- and technology-driven systems. This article examines the role of information management in improving learning quality through the strategic use of data for decision-making. A systematic literature review was employed, focusing on studies related to digital transformation, learning analytics, and data-driven decision-making in education. The findings indicate that the integration of information systems with analytical technologies enables a more comprehensive understanding of learners’ behavioral patterns. Systematic data utilization contributes to improved instructional effectiveness, learning personalization, and student engagement. However, implementation remains constrained by limited data literacy among educators, inadequate technological infrastructure, and ethical concerns in data governance. Within this context, information management functions as a strategic framework that integrates data collection, processing, and utilization to support evidence-based decision-making. Consequently, digital transformation should not be viewed merely as a technological shift, but also as a structural and cultural transformation within educational organizations. Optimizing information management is therefore essential to fostering adaptive and sustainable learning environments.